The Sustainable Innovation Impact of AI and Immersive Technology in Information System Management on Education Development - Hao, Long; Hao, Zhang (IC-ITECHS, 2024)
Abstract This paper describes the development of artificial intelligence and immersive technology in the field of education. The background of the research was introduced, including the analysis of its application in education from relevant international and domestic research. There are also application status, such as the data processing advantages of AI in education and the role of the squirrel Ai large model, as well as the pilot application of immersive technology in some fields and the improvement of the management of educational information systems. Then, the data generated by the integration of the two in the educational information system and the use of analysis are explained. It also highlights the sustainable innovations that this integration brings, such as optimizing resource allocation, improving educational effectiveness, reducing costs, and promoting educational equity. At the same time, it pointed out the challenges faced by technology convergence and proposed countermeasures to address these challenges.